Categorization of Family Services in the Russian Segment of Online Space (on the Example of “VKontakte” Page Accounts) - T. N. Zakharkina; A. I. Yanak (Управленческое консультирование)
The purpose of the work is to categorize and briefly describe online family services using the example of accounts on the VKontakte social network. The theoretical and methodological basis of the study was the concept of intensive motherhood, as well as the concept of professionalization of parenthood. According to the results of content analysis of information blocks of specialists’ profiles (n=52 pages/communities) offering certain products, services, content, the most common and, at the same time, in-demand areas and forms of activity of new support subjects and providers of special competencies of modern parents are identified: neuropsychology/ child psychology, informal/ non-institutionalized practices of preparation for childbirth, obstetric care and postpartum recovery, assistance in the organization of breastfeeding, sleep and nutrition of the child, replication of parental life hacks, exclusive methods of education, game practices. Providers of “new” services are, as a rule, parents (more often mothers) who have experienced certain difficulties in caring for/raising a child/children and are ready to broadcast, monetize their “unique” experience, which they subsequently confirmed and formalized (availability of specialized professional retraining or additional education). Online platforms are becoming a convenient and accessible channel for the reproduction and consumption of expert parental knowledge in the form of blogs, webinars, online intensive courses, etc. This opens up broad prospects for the further development of this segment of the services market. -